Use of Calcia Stabilized Zirconia and β-/β"-Alumina Solid Electrolytes in Galvanic Cells - Kumar, Vasant R. (My University, 1984)
Thermodynamic measurements were made using the following ionic materials as solid electrolytes in galvanic cells: calcia stabilized zirconia, Naβ and α-alumina, Caβ"-alumina, Kβ- and α-alumina, Laβ- and α-alumina, and Caβ and α-alumina. With the exception of the widely employed calcia stabilized zirconia, the ionic materials utilized in this work have only recently been developed as solid electrolytes. In order to characterize these β-/β"-aluminas for high temperature galvanic cell applications, their chemical stabilities were determined.
The following sections give a description of the various galvanic cells used in the present study, and a summary of the thermodynamic information obtained from each cell.
Calcia Stabilized Zirconia (and Naβ- and α-alumina) Solid Electrolytes in Galvanic Cells for Equlibrium Studies in M-S-O Systems
(M = Ca, Mg, La, K and Na)
The following electrochemical cells were used for thermodynamic equilibrium studies in metal-sulphur-oxygen systems:
Cell I
Pt⎮Cu(s), Cu₂S(s), CaS(s), CaO(s)⎮CSZ⎮Air⎮Pt
Cell II
Pt⎮CaS(s), CaSO₄(s)⎮CSZ⎮Air⎮Pt
Cell III
Pt⎮Cu(s), Cu₂S(s), CaSO₄(s), CaO(s)⎮CSZ⎮Air⎮Pt
Cell IV
Pt⎮Ag(s), Ag₂S(s), MgS(s), MgO(s)⎮CSZ⎮Air⎮Pt
Cell V
Pt⎮Ag(s), Ag₂S(s), MgS(s), MgO(s)⎮Naβ-and α-alumina⎮Ni(s), NiO(s)⎮Pt
Cell VI
Pt⎮Cu(s), Cu₂S(s), La₂O₂S(s), La₂O₃(s)⎮CSZ⎮Air⎮Pt
Cell VII
Pt⎮Ag(s), Ag₂S(s), La₂S₃(s), La₂O₂S(s)⎮CSZ⎮Air⎮Pt
Cell VIII
Pt⎮Ag(s), Ag₂S(s), La₂S₃(s), La₂O₂S(s)⎮Naβ-and α-alumina⎮Ni(s), NiO(s)⎮Pt
Cell IX
Pt⎮K₂S(s), K₂SO₄(s)⎮CSZ⎮Air⎮Pt
Cell X
Pt⎮Na₂S(s), Na₂SO₄(s)⎮CSZ⎮Air⎮Pt
The results from Cells I, III and VI were each combined with the values of ΔGfº for Cu₂S in order to calculate the ΔGº of the following reactions:
CaO + 1/2S₂→CaS + 1/2O₂ Cell I
CaO + 3/2O₂ + 1/2S₂→CaSO₄ Cell III
La₂O₃ + 1/2S₂→La₂O₂S + 1/2O₂ Cell VI
Cells II, IX and X were used to determine the standard free energies of oxidation of CaS, K₂S and Na₂S to their corresponding sulphates.
The results from cells IV and VII were each combined with the values of ΔGfº for Ag₂S to determine the ΔGº of the following reactions:
MgO + 1/2S₂→MgS + 1/2O₂ Cell IV
La₂O₂S + S₂→La₂S₃+ O₂ Cell VII
Cells V and VII were used to confirm that the oxygen pressures developed in the anodes of cells IV and VII were within the electrolytic domain of the CSZ solid electrolyte.
Thermodynamic Stabilities of β-/β"-Aluminas
CSZ solid electrolytes were also used to study the chemical stabilities of Caβ"-alumina, Laβ-alumina, Kβ-alumina, and Naβ-alumina. The following cells were employed in this investigation:
Cell XI
Pt⎮Ag(s), Ag₂S(s), CaSO₄(s)/(CaO)β-(s)⎮CSZ⎮Air⎮Pt
(CaO)β-(s) refers to Caβ-alumina in coexistence with MgO-Al₂O₃(s) and α-Al₂O₃(s).
The results from cell Xl were employed for determining the CaO activities in α-AI₂O₃(s)/MgO-AI₂O₃(s)/Caβ"-alumina coexistence.
Cell XII
Pt⎮Ag(s), Ag₂S(s), La₂O₂SO₄(s), (La₂O₃)β/α(s)⎮CSZ⎮Air⎮Pt
(La₂O₃)β/α refers to Laβ-alumina in coexistence with α-Al₂O₃
Cell XIII
Pt⎮Ag(s), Ag₂S(s), La₂O₂SO₄(s), (La₂O₃)β/ʟᴀ(s)⎮CSZ⎮Air⎮Pt
(La₂O₃)β/ʟᴀ refers to Laβ-alumina in coexistence with La₂O₃-Al₂O₃(s).
Cells XII and XIII were used to obtain the values of La₂O₃ activities in α- Al₂O₃/Laβ-Al₂O₃ and La₂O₃-Al₂O₃/Laβ-Al₂O₃ coexistences.
Cell XIV
Pt⎮Ag(s), Ag₂S(s), K₂S(s), (K₂O)β/α(s)⎮CSZ⎮Air⎮Pt
(K₂O)β/α refers to the Kβ-alumina in coexistence with α-Al₂O₃.
Cell XV
Pt⎮Ag(s), Ag₂S(s), Na₂S(s), (Na₂O)β/α(s)⎮CSZ⎮Air⎮Pt
(Na₂O)β/α refers to Naβ-alumina in coexistence with α-Al₂O₃.
The result from these two cells were utilized in order to calculate the respective alkali oxide activities in α-Al₂O₃/β-Al₂O₃ coexistences.
The thermodynamic stability of Caβ-alumina (CaO-6AI₂O₃) was determined by measuring the CaO activities in α-Al₂O₃/β-Al₂O₃ and CaO-2Al₂O₃/β-Al₂O₃ coexistences. These measurements were undertaken by using Caβ"-alumina as solid electrolyte in the following two calcium concentration cells:
Cell XVI
Pt⎮Air⎮CaO(s),Pt(s)⎮Caβ"-alumina⎮Pt(s),CaO-6Al₂O₃(s),α-Al₂O₃(s)⎮Air⎮Pt
Cell XVII
Pt⎮Air⎮CaO(s),Pt(s)⎮Caβ"-alumina⎮Pt(s),CaO-6Al₂O₃(s),CaO-2Al₂O₃(s)⎮Air⎮Pt
Thermodynamics of CaO-AI₂O₃ System Using Caβ"-Alumina Solid Electrolyte
Caβ"-alumina solid electrolytes were utilized to measure the CaO activities in the CaO-Al₂O₃ system in the following cells (in addition to cells XVI and XVII):
Cell XVIII
Pt⎮Air⎮CaO(s),Pt(s)⎮Caβ"-alumina⎮Pt(s),CaO-Al₂O₃(s),CaO-2Al₂O₃(s)⎮Air⎮Pt
Cell XIX
Pt⎮Air⎮CaO(s),Pt(s)⎮Caβ"-alumina⎮Pt(s),3CaO-Al₂O₃(s),CaO-Al₂O₃(s)⎮Air⎮Pt
Cell XX
Pt⎮Air⎮CaO(s),Pt(s)⎮Caβ"-alumina⎮Pt(s),CaO(s),3CaO-Al₂O₃(s)⎮Air⎮Pt
Two-Phase β- and α-Alumina Solid Electrolytes in Oxygen Concentration Cells
The reversibility of two phase β- and α-alumina solid electrolytes to oxygen potentials were tested using the following cells:
Cell XXI
Pt⎮Fe(s), FeO(s)⎮Naβ- and α-alumina⎮Ni(s), NiO(s)⎮Pt
Cell XXII
Pt⎮Fe(s), FeO(s)⎮Kβ- and α-alumina⎮Ni(s), NiO(s)⎮Pt
Cell XXIII
Pt⎮Fe(s), FeO(s)⎮Laβ- and α-alumina⎮Ni(s), NiO(s)⎮Pt
Cell XXIV
Pt⎮Fe(s), FeO(s)⎮Caβ- and α-alumina⎮Ni(s), NiO(s)⎮Pt
Applications
(i) The data obtained from cells I to X were used to construct the metal- sulphur-oxygen phase stability diagrams at high temperature for the elements Ca, Mg, La, K and Na.
(ii) The phase stability diagrams for Ca-S-O, La-S-O, K-S-O and Na-S-O systems were further extended by including the data for CaO-Al₂O₃ systems (cells XI, XVI to XX),, La₂O₃-Al₂O₃ system (cells XII and XIII), Kβ-alumina (cell XIV) and Naβ-alumina (cell XV) respectively.
(iii) The thermodynamic information from the phase stability diagrams for Ca-S-O (extended), Mg-S-O and La-S-O (extended) were combined with available data in the literature to construct deoxidation- desulfurization diagrams for liquid iron at 1643K and liquid steel at 1873K.
(iv) The results for the chemical stabilities of β/β"-aluminas (cells XI to XVII) were extrapolated to different conditions of temperatures and oxygen partial pressures. These results were used to determine the feasibility of their utilization as solid electrolytes in galvanic cells for industrial applications in iron and steelmaking.
Keywords: Metallurgy; Metallurgy